Salivary interleukin-6 levels in children with early childhood caries and ventricular septal defect - Tinu George; Parvathy Kumaran; R Balagopal Varma; Arun Mamachan Xavier; Suresh Kumar Janardhanan; Bhat Sangeetha Govinda (Wolters Kluwer Medknow Publications, 2018)
Background: The efficacy of dental treatment on the levels of inflammatory markers in ventricular septal defect (VSD) has not been fully explored. Aims: The aim of this study was to assess the level of salivary interleukin-6 (IL-6) in children with early childhood caries (ECC) and VSD and to compare its levels before and after comprehensive full mouth rehabilitation. Methods: Saliva samples were collected from children with ECC and VSD before dental treatment and 1-month posttreatment. The salivary IL-6 levels were analyzed using the enzyme-linked immunosorbent assay method. Gingival index (GI) was also timely recorded during the study period. Oral health awareness sessions were conducted for children and their parents. The Fisher's Least Significant Difference test was used for intergroup comparison of salivary IL-6 levels, while the paired t-test compared the values of GI before and after treatment. Results: The mean salivary IL-6 levels 1 month after treatment had reduced (P < 0.000). There was a reduction in GI score (P = 0.002). Conclusions: When children having VSD and ECC are dentally rehabilitated and followed up periodically, the level of IL-6 is minimized, hence improving the quality of life of the affected children.